2004
DOI: 10.1038/sj.eye.6701416
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of emergency argon laser retinopexy performed by trainee doctors

Abstract: Objective To report the outcomes following treatment of retinal tears with argon laser photocoagulation by trainee doctors as an emergency procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
13
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 9 publications
7
13
1
1
Order By: Relevance
“…Untreated retinal tears progress to RD in 30-50% of cases [3,4], and laser retinopexy has long been established as an effective means of reducing this risk [5]. A rate of progression to RD after laser retinopexy of 2-8.8% has been reported [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Untreated retinal tears progress to RD in 30-50% of cases [3,4], and laser retinopexy has long been established as an effective means of reducing this risk [5]. A rate of progression to RD after laser retinopexy of 2-8.8% has been reported [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The studies on prophylactic laser retinopexy performed by residents [10,11] demonstrated a high rate of cases requiring repeated or additional treatment and indicate the need for structured supervised training of residents in performing this procedure. Review of the literature revealed few studies focused on designing simulators for retinal laser photocoagulation, based on virtual reality technology [14,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Levin et al [10] have shown that 15% of laser retinopexy procedures performed by residents were inadequate and required retreatment. Ghosh et al [11] have reported that 24% of laser retinopexy procedures performed by residents were inadequate and required retreatment. Additionally, 8% of the patients with retinal breaks who were treated by residents had progressed and required surgery within a few weeks of the prophylactic laser treatment, a much higher rate than that reported for experienced ophthalmologists (3.8% in over 5 years of follow-up) [12].…”
Section: Introductionmentioning
confidence: 99%
“…This may indicate an increase in the pathogenicity of the organism or, as is not uncommon in head and neck fasciitis, the presence of more than one infective agent, the other agent having been successfully treated with flucloxacillin and benzylpenicillin. Diagnosis of necrotizing fasciitis is based on the clinical presentation of pain, erythema, skin necrosis, and oedema, with subsequent histological findings of extensive fascial and subcutaneous tissue necrosis, 1 which the above case clearly demonstrated. Due to the increasing prevalence of B-lactamase producing Moraxella strains, explaining the poor response to initial antibiotic treatment, the recommended antibiotic regime is now co-amoxyclav or a cephalosporin (first, second or third generation) on recognition of, or when there is a suspicion of, Moraxella infection.…”
Section: Commentmentioning
confidence: 99%
“…1 While necrotizing fasciitis classically involves the trunk, groin, and lower limbs, primary involvement of the eyelids is a well-known entity. 2,3 We describe the first report of Moraxella species being the causative organism in a case of necrotizing fasciitis.…”
Section: Moraxella As a Cause Of Necrotizing Fasciitis Of The Eyelidmentioning
confidence: 99%